2012
DOI: 10.1142/s0218810412500256
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Signs of Static Carpal Instability With Distal End Radius Fractures: Is Current Treatment Adequate?

Abstract: Patients presenting with distal end radius fractures may have concomitant carpal instability due to disruption of the scapholunate ligament. This study examined the incidence of static radiographic signs of carpal instability in patients with distal radial fractures before and after fracture treatment. We performed a retrospective radiographic study of 141 patients presenting to Central Middlesex Hospital, London between January 2002-May 2004 with distal end radius fractures. We used abnormal scapholunate angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…However, these are not always clinically relevant. Possibly, ligamentous healing takes place during the immobilization [ 4 , 18 , 19 ]. Nonetheless, some patients receive simultaneous open distal radius fixation and direct SLIL reconstruction [ 20 - 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these are not always clinically relevant. Possibly, ligamentous healing takes place during the immobilization [ 4 , 18 , 19 ]. Nonetheless, some patients receive simultaneous open distal radius fixation and direct SLIL reconstruction [ 20 - 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that patients with abnormal scapholunate angles at the time of presentation may have signs of static scapholunate dissociation at final followup, signifying the high morbidity of these injuries if left untreated. 43 Advocates of arthroscopically assisted fracture reduction techniques for DRF often cite the ability to acutely diagnose and treat SLIL injuries. In a retrospective review of 26 wrists treated exclusively with arthroscopically assisted fracture fixation using K-wires, the authors also treated 19 SLIL and 10 LTIL injuries.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Distal radius fractures often have concomitant carpal bone diastases, specifically scapholunate (SL) dissociation due to disruption of the scapholunate ligament [3][4][5]. Bunker et al reported that 39% of the patients with distal radius fractures had abnormal SL angles [5]. Moreover, Pilný et al reported that SL instability associated with type B fracture was found in 25% of the patients [6].…”
Section: Discussionmentioning
confidence: 99%